2020
DOI: 10.1177/1471301220933121
|View full text |Cite
|
Sign up to set email alerts
|

Carers Create: Carer perspectives of a creative programme for people with dementia and their carers on the relationship within the (carer and cared-for) dyad

Abstract: Introduction Relationships between people with dementia and their carers can prove challenging over the trajectory of the disease. Interventions with a potential to address this include arts and music-based activities. This research project aimed to evaluate a community engagement programme (Carers Create) where both people with dementia and their carers participate together in singing and other activities. A specific focus was on the impact of the sessions on the dya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Based on our results, a combination of various arts was experienced as the most effective. Previously, art gallery viewing and group singing (Osman et al, 2016;Skingley et al, 2020) showed promising results. However, our results do not fully confirm that activities that allow active learning give hope and relief to daily life and increased self-confidence to do something constructive, as reported in previous studies (Bourne et al, 2021;Van't Leven et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on our results, a combination of various arts was experienced as the most effective. Previously, art gallery viewing and group singing (Osman et al, 2016;Skingley et al, 2020) showed promising results. However, our results do not fully confirm that activities that allow active learning give hope and relief to daily life and increased self-confidence to do something constructive, as reported in previous studies (Bourne et al, 2021;Van't Leven et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…According to Ward et al ( 2020 ), participatory art aims to promote health and well‐being without focusing on the health condition. Moreover, participating in art groups positively influences the relationships between carer and cared‐for (Skingley et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst there is evidence suggesting shared arts experiences yield benefits for both carers and the cared-for 5,[28][29][30] , previous research on the impact of intergenerational arts practice has tended to focus on the 'end users' of projects. However, it is important to examine those in supporting roles (i.e.…”
Section: Introductionmentioning
confidence: 99%